Ancient models in the early modern Republican imagination - Velema, Wyger; Weststeijn, Arthur (Metaforms, 2018)
Ancient Models in the Early Modern Republican Imagination offers a new approach to the study of the classical dimensions of early modern republican thought by analysing its specific and concrete uses of ancient republican models.